Development of a Portable Tool for Screening Neuromotor Sequelae From Repetitive Low-Level Blast Exposure. (1st March 2017) - Rhea, Christopher K.; Kuznetsov, Nikita A.; Ross, Scott E.; Long, Benjamin; Jakiela, Jason T.; Bailie, Jason M.; Yanagi, Matthew A.; Haran, F. Jay; Wright, W. Geoffrey; Robins, Rebecca K.; Sargent, Paul D.; Duckworth, Joshua L.
ABSTRACT: Blast exposure is a prevalent cause of mild traumatic brain injury (mTBI) in military personnel in combat. However, it is more common for a service member to be exposed to a low-level blast (LLB) that does not result in a clinically diagnosable mTBI. Recent research suggests that repetitive LLB exposure can result in symptomology similar to symptoms observed after mTBI. This manuscript reports on the use of an Android-based smartphone application (AccWalker app) to capture changes in neuromotor functioning after blast exposure. Active duty U.S. Navy personnel ( N = 59) performed a stepping-in-place task before repetitive LLB exposure (heavy weapons training), and again immediately after, 24 hours after, and 72 to 96 hours after the completion of the training. The AccWalker app revealed that there are changes in neuromotor functioning after LLB exposure (slower self-selected movement pace and increased stride time variability) in participants who experienced neurocognitive decline. These data suggest that neurocognitive and neuromotor decline can occur after repeated LLB exposure.